Tests improve memory – no matter if you feel good or bad while taking them. Issue 8 (14th September 2019) - Emmerdinger, Kathrin J.; Kuhbandner, Christof
ABSTRACT: Based on studies demonstrating that testing promotes better long-term retention than restudying (i.e., the testing effect), testing has been recommended as a powerful tool to boost knowledge acquisition in educational settings. However, a factor ubiquitous in real-life learning contexts has been ignored to date: the learner's affective state. To examine whether the learner's affective state influences the testing effect, we conducted two experiments. We employed a standard testing-effect paradigm consisting of an initial study phase and a subsequent restudy/testing phase, and induced negative, neutral, or positive affective states either before participants initially studied short expository texts (Experiment 1) or before they restudied or were tested on them (Experiment 2). After one week, memory for the texts was tested. In both experiments, previously tested material was better remembered than previously restudied material. However, in none of the experiments, did the memory advantage of testing over restudying vary as a function of affect condition. Hence, the present results suggest that testing seems to benefit long-term retention independently of the learner's affective state.